2018
DOI: 10.18203/issn.2455-4510.intjresorthop20184711
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of symptomatic deep vein thrombosis and pulmonary embolism, following THA in patients, with postoperative chemoprophylaxis in Indian population

Abstract: <p class="abstract"><strong>Background:</strong> Deep vein thrombosis (DVT) and pulmonary embolism (PE) can occur in patients after elective total hip arthroplasties (THA). Indian population appears to have low incidence of DVT and PE in comparison with Western population due to difference in ethnicity, genetic make-up, social life styles. The study intends to find the incidence of symptomatic DVT and PE in postoperative THA patients. The aim of the study was to study the incidence of symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…(Figure 2). Low prevalence was stated in studies by Jain et al (2004); Bagaria et al (2006); Dore et al (2017) and Avulapati et al (2019). In the prospective study by Jain et al there were a total of 2 patients who had developed venous thromboembolism out of 60 THR in 45 patients and 46 TKR in 26 patients (2.8%).…”
Section: Orthopedic Surgerymentioning
confidence: 95%
See 1 more Smart Citation
“…(Figure 2). Low prevalence was stated in studies by Jain et al (2004); Bagaria et al (2006); Dore et al (2017) and Avulapati et al (2019). In the prospective study by Jain et al there were a total of 2 patients who had developed venous thromboembolism out of 60 THR in 45 patients and 46 TKR in 26 patients (2.8%).…”
Section: Orthopedic Surgerymentioning
confidence: 95%
“…Interestingly, in Bagaria et al study out of 147 patients undergoing THR and TKR, 9 patients (6.12%) had VTE, out of which PE was 0.6%. Whereas among the total of 101 patients 8 patients (7.92%) had developed DVT and 2 of these patients had complications of PE (Dore et al, 2017;Avulapati et al, 2019) revealed a different aspect in their retrospective study, with the prevalence of symptomatic DVT as low as 0.22% (1 out of 447 patients) and PE 0%.…”
Section: Orthopedic Surgerymentioning
confidence: 95%